Deconstructing the cultural confinement of the Western menopausal women towards a spirituality of liberation - Meletiou, Crystal (Verbum et ecclesia, 2015)
Throughout the ages, menstruation and menopause have posed unique challenges in the life of women. In Biblical times, much was said about the impurity of a menstruating woman. In the past century, however, the focus gradually shifted to menopause and the effect thereof on a woman's body, both aesthetically and physiologically. Freud went so far as to argue that menopausal women are neurotic and that an oophorectomy (the surgical removal of the female ovaries) should be a standard procedure for a menopausal woman. Unfortunately, this Freudian theory has not yet been completely demolished in our contemporary society. Hysterectomies (the surgical removal of the uterus) are still frequently performed on menopausal women, and all too often, antidepressants are included in menopausal women' medical regimes. The question remains: Can hysterectomy, hormone replacement therapy and antidepressants erase' the challenges that Western menopausal women face?Intradisciplinary and/or interdisciplinary implications: Western menopausal women are under tremendous social pressure to preserve their youthfulness. Many middle-aged women live with the fear that their declining sexual appeal may result in rejection, both personally and professionally. Unfortunately, the intellectual value of these women is seldom acknowledged.